How Do Russians Perceive and Justify the Status Quo: Insights From Adapting the System Justification Scales - Elena Agadullina; Alexander Ivanov; Irena Sarieva (Frontiers in Psychology, 2021)
This paper aims to adapt the system justification scales (general, political, economic, and gender) for the Russian socio-cultural context and to carry out their psychometric analysis. In Study 1 (N = 450), the original items from four system justification scales on a Russian sample were tested. The results suggested that none of the original scales worked properly in Russia and all of them demonstrated weak fit indices. In Study 2 (N = 553), culturally specific grounds for system justification in the Russian context were highlighted and tested. The results of this study confirmed that all the adapted scales demonstrated a good fit to the data. In Study 3 (N = 1,011), the invariance of system justification scales and the convergent and discriminant validity of the scales was tested. The results confirmed that the general, political, and economic system justification scales demonstrated full invariance, while the gender system justification scale showed partial invariance for multigroup comparison. All the scales convergent and discriminant validity, which leads to consider them as an effective tool for measuring system justification in various types of social relationships in Russia. The role of socio-cultural characteristics in justifying the status quo is discussed.